Delayed pull‐through coloanal anastomosis without temporary stoma: an alternative to the standard manual side‐to‐end coloanal anastomosis with temporary stoma? A comparative study in 223 patients with low rectal cancer. (10th February 2022) - Melka, Dan; Leiritz, Elsa; Labiad, Camélia; Blondeau, Marc; Frontali, Alice; Giacca, Massimo; Monsinjon, Marie; Panis, Yves
Abstract: Aim: After total mesorectal excision (TME) for low rectal cancer, current guideline recommendations for sphincter‐saving surgery are to perform a side‐to‐end manual coloanal anastomosis (CAA) (or with J‐pouch) with a temporary stoma. Our study aimed to evaluate if delayed pull‐through coloanal anastomosis (DCAA) without a temporary stoma could represent a safe alternative in low rectal cancer. Method: From 2003 to 2020, 223 consecutive patients with low rectal cancer undergoing TME were compared: CAA and diverting stoma ( n  = 190) versus DCAA without stoma ( n  = 33). Results: Overall 3‐month and severe (Dindo ≥ IIIb) morbidity rates were similar in CAA versus DCAA groups: 34% (65/190) vs. 36% (12/33) and 2.6% (5/190) vs. 3% (1/33), respectively. In the DCAA group, only one patient (3%) underwent reoperation (Hartmann's procedure) at day 3 due to colon necrosis. The anastomotic leakage rate (both clinical and radiological) was significantly higher after CAA than DCAA: 28% (53/190) vs. 3% (1/33; p  = 0.00138). Failure of the procedure (with return to stoma) was observed in 8% (15/190) vs. 6% (2/33) of patients after CAA and DCAA respectively (not significant). Conclusion: Our comparative study suggested that in patients with low rectal cancer, DCAA without a temporary stoma could represent an interesting alternative to the actual recommended CAA with a temporary ileostomy. DCAA could offer two major advantages over CAA: a significantly lower rate of anastomotic leakage and absence of a temporary stoma and its potential complications (rehospitalization, dehydration, wound hernia after stoma closure).